The veterinary medicinal products market supply gap: A practical insight based on the Regulation (EU) 2019/6 - Nogueira, Rafaela; Baptista, Catarina Jota; Gonçalves, Lio; Coelho, Ana Claúdia; Faustino-Rocha, Ana I.; Regueiro Purriños, Marta; Gonzalo-Orden, José M.; Oliveira, Paula A. (Revista de Ciências Agroveterinárias, 2024)
The Regulation (EU) 2019/6 establishes that the veterinary prescriptions should follow a cascade, according to their availability of the market. In sum, the veterinarian is authorized to use a medicine for human use only if there is no product available for the same or other therapeutic indication, in the same or another animal species. This study aims to analyse the application of Regulation (EU) 2019/6 in the pharmacological prescription at the Veterinary Hospital of the University of León. A total of 121 clinical cases, 89 dogs (73.55%) and 32 cats (26.45%) were included. Results revealed that 95 medicines were prescribed, 51 (53.68 %) as veterinary medicines and 44 (46.32 %) as human medicines. From the human medicines, 22 (50.00%) did not have a veterinary alternative in the market; four (9.00%) presented a veterinary medicine in the appropriate formulation for the species; 10 (23.00%) had no alternative in the desired formulation; and 8 (18.00%) had no alternatives for the target species. This study suggested that the cascade was not strictly followed, and several reasons may justify it, such as the lack of veterinary products, different formulations, and differences in costs. An effective, safe and sustainable use of the therapeutic option available can only be accomplished with a rational use of the prescription cascade and a correct use of the Regulation (EU) 2019/6.